Epidemiology, clinical characteristics and treatment of critically ill patients with COVID-19): a protocol for a living systematic review. Issue 1 (5th January 2021) - Milovanovic, Lazar; Hessey, Erin; Sebastianski, Meghan; Keto-Lambert, Diana; Vandermeer, Ben; Bagshaw, Sean M; Rewa, Oleksa
Abstract : Introduction: In December 2019, the first cases of COVID-19 associated with SARS-CoV-2 viral infection were described in Wuhan, Hubei Province, China. Since then, it has spread rapidly affecting 188 countries and was declared a pandemic by the WHO on 11 March 2020. Preliminary reports suggest up to 30% of patients require intensive care unit (ICU) admission and case fatality rate estimate is 2.3%–7.2%. The primary reason for ICU admission is hypoxaemic respiratory failure, while factors associated with ICU admission include increased age, presence of comorbidities and cytokine storm. Case series and retrospective trials initially assessed proposed treatments with randomised controlled trials now reporting early outcomes. We conduct a systematic review and meta-analysis to identify epidemiological factors, treatments and complications that predict mortality among critically ill patients with COVID-19. Methods and analysis: Our comprehensive search strategy was developed in consultation with a research librarian. We will search electronic databases: Ovid Medline, Ovid Embase, Ovid Cumulative Index to Nursing and Allied Health Literature (CINAHL) and Wiley Cochrane Library. The search strategy combines concepts from COVID-19, validated COVID-19 search filters and geographical locations of large outbreaks. Citation screening, selection, quality assessment and data abstraction will be performed in duplicate. Clinically homogenous epidemiological characteristics, interventions and complications will be pooled in statistical meta-analysis. Within the framework of a living systematic review, the search and data analysis will be updated every 6 months. Ethics and dissemination: Our systematic review will synthesise literature on risk factors and interventions associated with mortality in critically ill patients with COVID-19. Results will be presented at national and international conferences and submitted for peer-reviewed publication. The pooled analysis can provide guidance to inform clinical guidelines for care of critically ill patients with COVID-19. Iterative updates will be made public through open access. Research ethics approval is not required. PROSPERO registration number: CRD42020176672.